2013
DOI: 10.1002/pca.2429
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid and Derivatives from Cochlospermum angolensis Welw. Extracts: HPLC–DAD–ESI/MSn Profiling, Quantification and In Vitro Anti‐depressant, Anti‐cholinesterase and Anti‐oxidant Activities

Abstract: The results provided evidence of the value of C. angolensis as a source of health-promoting anti-oxidants and anti-depressant compounds, with potential to be used as a raw product for food and pharmaceutical industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…Similarly, erythrocytes obtained from mice infected with P. berghei , showed immediate inhibition of parasite DNA replication and protein expression after exposure to borututu extract [4]. In a recent study, Ferreres et al demonstrated a significant antioxidant activity of different borututu extracts, which was attributed to ellagic acid and related analogs [5]. Similarly, Pereira et al showed that a boiling water infusion of borututu bark showed antioxidant and antitumor activity [2].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, erythrocytes obtained from mice infected with P. berghei , showed immediate inhibition of parasite DNA replication and protein expression after exposure to borututu extract [4]. In a recent study, Ferreres et al demonstrated a significant antioxidant activity of different borututu extracts, which was attributed to ellagic acid and related analogs [5]. Similarly, Pereira et al showed that a boiling water infusion of borututu bark showed antioxidant and antitumor activity [2].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the chemical composition of these plants is not constant and the presence of chemicals that claims to have medicinal benefits (active principals) depends on a number of factors including the plant species, the time and season of harvest, the type of soil, the way the herb is prepared, etc. (Ferreres et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless and despite the high consumption of those plants, the studies on nutritional value and primary metabolites are scarce, being only reported their phytochemical composition in non-nutrients such as phenolic compounds (Kukić et al 2008;Wang et al 2010;Abu-Reidah et al 2013;Ferreres et al 2013). …”
Section: Introductionmentioning
confidence: 99%